Single‐center experience of ultra‐high‐density mapping guided catheter ablation of focal atrial tachycardia. Issue 3 (12th January 2022) - Kellnar, Antonia; Fichtner, Stephanie; Mehr, Michael; Czermak, Thomas; Sinner, Moritz F.; Lackermair, Korbinian; Estner, Heidi L.
Abstract: Introduction: Catheter ablation is the treatment of choice for recurrent focal atrial tachycardia (FAT) as medical therapy is limited. Routinely, a three‐dimensional mapping system is used. Whether or not optimized signal detection does improve ablation success rates has not yet been investigated. This retrospective cohort study compared ablation procedures using an ultra‐high‐density mapping system (UHDM, Rhythmia, Boston Scientific) with improved signal detection and automatic annotation with procedures using a conventional electroanatomic mapping system (CEAM, Biosense Webster, CARTO). Methods: All patients undergoing ablation for FAT using UHDM or CEAM from April 2015 to August 2018 were included. Endpoints comprised procedural parameters, acute success as well as freedom from arrhythmia 12 months after ablation. Results: A total of 70 patients underwent ablation (48 with UHDM, 22 with CEAM). No significant differences were noted for parameters like procedural and radiation duration, area dose, and RF applications. Acute success was significantly higher in the UHDM cohort (89.6% vs. 68.2%, p = .03). Nevertheless, arrhythmia freedom 12 months after ablation was almost identical (56.8% vs. 60%, p = .87), as more patients with acute success of ablation presented with a relapse during follow‐up (35.0 vs. 7.7%, p = .05). Conclusion: Acute success rate of FAT ablation might be improved by UHDM, without an adverse effect on procedural parameters. Nevertheless, further research is needed to understand the underlying mechanism for increased recurrence rates after acute successful ablation.